# Rewrite formula in terms of

This is a homework question but I don't want the answer. I just want to know if I'm right or wrong to see if I understand what I'm doing.

Need to rearrange this in terms of d

$a = b \times c + b \times d$

My answer is: $\frac{(a - bc)}{b} = d$

Is that correct?

If not any hints or resources would help. I've used KhanAcademy which seems good.

Thanks!

• Yes , It is correct – Peđa Terzić Sep 11 '15 at 16:06
• It is correct :). – Chinny84 Sep 11 '15 at 16:07
• Great thanks! :) – user269914 Sep 11 '15 at 16:07

To close this question off with an answer $$a = bc +bd = bd + bc$$ so lets try to make $d$ the subject by bringing everything to one side with the exception of the terms with $d$ in it. $$a - bc = bd + bc - bc = bd + 0 = bd$$ now we have a term on the right hand side $b\times d$, and what is the opposite of multiplication? it is division so we can divide both sides by $b$ $$(a-bc)\div b = (b\times d)\div b = d$$ and then you are done $$\frac{a-bc}{b} = d$$ now this is the result you require (and you correctly obtained so well done!!) Now from my experience some students have an issue of seeing that $$\frac{a-bc}{b} = d$$ is the same or equivalent to $$d = \frac{a-bc}{b}$$ (just in case)